PENINGKATAN PERTUMBUHAN TANAMAN SAWI HIJAU (Brassica juncea) DI TANAH MARGINAL MELALUI APLIKASI PUPUK HAYATI Trichoderma sp. - Sumini, Sumini; Kriswantoro, Haris; Khairunisa, Dinda (Universitas Muhammadiyah Bengkulu, 2024)
This research aimed to determine the increase in green mustard growth on marginal land through the application of trichoderma sp biofertilizer. This research was carried out in Muara Enim Village, West Lubuklinggau I District, Lubuklinggau City from July to September 2024. This research used a non-factorial randomized block design with 6 levels of treatment, namely: T0: No application of biological fertilizer (control), T1: Application of biological fertilizer at a dose of 60 grams/polybag, T2: Application of biological fertilizer at a dose of 100 grams/polybag, P3: Application biofertilizer dose 140 grams/polybag, T4: Application of biofertilizer dose 180 grams/polybag, T5: Application of biofertilizer dose 220 grams/polybag. The research results showed that trichoderma sp biological fertilizer has a very real influence on the growth of mustard greens on marginal land. Providing trichoderma sp biological fertilizer at a dose of 220 grams/polybag was able to show the best results at plant height, namely 31.03 cm, number of leaves 16.50, leaf length 20.27 cm, leaf width 13.01 cm and root length 35 .91 cm. The application of trichoderma sp biological fertilizer is not only able to increase soil fertility but is also able to protect plants from soil pathogens. Keywords: Microorganisms, Pathogens, Trichoderma sp.